Water resource management at district level. First results of AQUATER research project - Rinaldi M.; Acutis M.; Castrignanò A.; D'Urso G.; Mastrorilli M.; Mattia F.; Rana G.; Ventrella D. (Irrigation in Mediterranean agriculture: challenges and innovation for the next decades, 2008)
An efficient management of water resources is a crucial point for Italy and in particular for Southern areas characterized by Mediterranean climate in order to improve the economical and environmental sustainability of the agricultural activity. AQUATER is a research project funded by the Italian Ministry of Agriculture, Food and Forestry Policies (2005-2009). It aims at developing a decision support system able to integrate remote sensing information and crop simulation model to allow a best management of irrigation water at district scale. It is focused on the remote sensing, the plant and the climate and, for interdisciplinary relationships, the project working group consists of agronomists, engineers and physicists. The Project is structured in four workpackages with specific objectives, high degree of interaction and information exchange: 1) Remote sensing and image analysis; 2) Cropping systems; 3) Modelling and softwares development; 4) Stakeholders. In the paper the main results of the first two years of the Project are reported and briefly commented.
International Conference on Irrigation in Mediterranean Agriculture: Challenges and Innovation for the Next Decades, 2008/06/17-18, Naples (Italy)